METODE PEMBELAJARAN TAHSIN AL-QUR’AN DALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR’AN PADA PONDOK PESANTREN JAMIAH AL- AZIZIYAH BATEE ILIEK SAMALANGA KABUPATEN BIREUN - Muhammad Reza (Jurnal Ikhtibar Nusantara, 2026)
This study aims to analyze the tahsin Al-Qur’an learning method in improving the Qur’an reading ability of students at Pondok Pesantren Jamiah Al Aziziyah Batee Iliek, Bireuen Regency. This research is motivated by the importance of the ability to read the Qur’an properly and correctly in accordance with tajwid rules, as well as the need for effective tahsin learning methods to improve the quality of students’ Qur’an recitation. This study employed a qualitative approach using a case study design. Data collection techniques included interviews, observations, and documentation. The research participants consisted of the pesantren leaders, tahsin Al-Qur’an teachers, and students participating in tahsin learning activities. The data were analyzed through the stages of data reduction, data presentation, and conclusion drawing.The results showed that the tahsin learning methods implemented at Pondok Pesantren Jamiah Al Aziziyah Batee Iliek included talaqqi, musyafahah, habituation of Qur’an recitation, and periodic evaluation of recitation. The implementation of these methods was able to improve students’ Qur’an reading abilities, particularly in aspects of makharijul huruf, reading fluency, and the application of tajwid rules. In addition, the teacher’s role in providing intensive guidance and motivation became a supporting factor for the success of tahsin learning. The findings of this study contribute to the development of Qur’an learning methods in Islamic boarding schools. This study concludes that structured and continuous tahsin learning methods are effective in improving students’ Qur’an reading abilities. Therefore, strengthening the competence of tahsin teachers and developing more innovative learning methods are necessary to enhance the quality of Qur’an learning in pesantren.